MD simulations reveal the basis for dynamic assembly of Hfq-RNA complexes - Krepl, Miroslav; Dendooven, Tom; Luisi, Ben F; Sponer, Jiri (The Journal of biological chemistry, 2021)
The conserved protein Hfq is a key factor in the RNA-mediated control of gene expression in most known bacteria. The transient intermediates Hfq forms with RNA support intricate and robust regulatory networks. In Pseudomonas, Hfq recognizes repeats of adenine-purine-any nucleotide (ARN) in target mRNAs via its distal binding side, and together with the catabolite repression control (Crc) protein, assembles into a translation-repression complex. Earlier experiments yielded static, ensemble-averaged structures of the complex, but details of its interface dynamics and assembly pathway remained elusive. Using explicit solvent atomistic molecular dynamics simulations, we modeled the extensive dynamics of the Hfq-RNA interface and found implications for the assembly of the complex. We predict that syn/anti flips of the adenine nucleotides in each ARN repeat contribute to a dynamic recognition mechanism between the Hfq distal side and mRNA targets. We identify a previously unknown binding pocket that can accept any nucleotide and propose that it may serve as a 'status quo' staging point, providing nonspecific binding affinity, until Crc engages the Hfq-RNA binary complex. The dynamical components of the Hfq-RNA recognition can speed up screening of the pool of the surrounding RNAs, participate in rapid accommodation of the RNA on the protein surface, and facilitate competition among different RNAs. The register of Crc in the ternary assembly could be defined by the recognition of a guanine-specific base-phosphate interaction between the first and last ARN repeats of the bound RNA. This dynamic substrate recognition provides structural rationale for the stepwise assembly of multicomponent ribonucleoprotein complexes nucleated by Hfq-RNA binding.
Keywords: Protein Binding; bakteriální RNA; ARN repeats; nukleotidové motivy; dynamic recognition; Nucleic Acid Conformation; vazebná místa; Host Factor 1 Protein; Crc protein; molecular dynamics; Hfq protein; regulace genové exprese u bakterií; RNA metabolism; vazba proteinů; Binding Sites; konformace nukleové kyseliny; Pseudomonas aeruginosa; konformace proteinů; RNA-binding protein; protein–nucleic acid interaction; Nucleotide Motifs; Protein Conformation; protein hostitelského faktoru 1; RNA, Bacterial; Gene Expression Regulation, Bacterial